On the relationship between household wealth and entrepreneurship - LEE, Jungho (Institutional Knowledge at Singapore Management University, 2017)
Motivated by a substantial number of startup owners with negative household net worth, I present a model that incorporates credit borrowing into Evans and Jovanovic [1989]. The estimated model generates no relationship between household wealth and the propensity for business entry. Ignoring credit borrowing for potential business owners substantially overstates the efficiency loss from financial constraints in business entry. However, the efficiency loss in investments by the entrants is large even if credit borrowing is allowed. Individuals who start a business once credit borrowing is available are those whose business ideas are of a high-enough quality to compensate high financing costs associated with credit borrowing. They start a business with a sub-optimal amount of investments, and those agents’ unrealized investments are considerable.